PENGUATAN INSPEKTORAT SEBAGAI LEMBAGA PENGAWAS DALAM TATA KELOLA PEMERINTAHAN DAERAH (STUDI PROVINSI MALUKU UTARA) - Slamat; Nam Rumkel; Tri Syafari (Sekolah Tinggi Ilmu Hukum Awang Long, 2019)
The position of the inspectorate as a supervisory body in the governance of regional government must be strengthened by the government making its own law. This is important in order to realize local governance, one of which is that it can prevent corruption must be accompanied by the strengthening of the inspectorate institution, through a separate Act with the Government's Internal Oversight System that can be accounted for. In order for authority, duties and functions to function as expected, regulations that must clearly regulate the position of the inspectorate in a regional government structure clearly match their role. Factors that play a role in strengthening the inspectorate as a supervisory institution in regional governance, must be born a separate law with the Government's Internal Monitoring System, which is not only at the center but also in the regions. Thus, the various strength factors become the strengthening of the inspectorate as a supervisory institution that can realize good and correct local governance.